2005
DOI: 10.1111/j.1475-097x.2005.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hormone replacement therapy and/or exercise on skeletal muscle attenuation in postmenopausal women: a yearlong intervention

Abstract: Hormone replacement therapy (HRT) has been reported to exert a positive effect on preserving muscle strength following the menopause, however, the mechanism of action remains unclear. We examined whether the mechanism involved preservation of muscle composition as determined by skeletal muscle attenuation. Eighty women aged 50-57 years were randomly assigned to either: HRT, exercise (Ex), HRT+exercise (ExHRT), and control (Co) for 1 year. The study was double-blinded with subjects receiving oestradiol and nore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 44 publications
(120 reference statements)
2
74
0
1
Order By: Relevance
“…Previous research has either found 10,11,32 or not found effects of HRT on muscle voluntary force 12,33,34 (see also 14 ). The reasons for the contradictions may come from several factors.…”
Section: Discussionmentioning
confidence: 91%
“…Previous research has either found 10,11,32 or not found effects of HRT on muscle voluntary force 12,33,34 (see also 14 ). The reasons for the contradictions may come from several factors.…”
Section: Discussionmentioning
confidence: 91%
“…HRT maintains the power output to a greater extent than isometric strength in postmenopausal women [31]. Using axial CT scans of the mid-thigh, Taaffe [32] showed that HRT preserves or improves skeletal muscle attenuation in early postmenopausal women, and has a positive effect on muscle performance. In our study, we did not observe any difference in muscle strength related to HRT, but our measurements were done at the biceps, which might not reflect muscle strength in the trunk.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that hormone replacement therapy (HRT) prevents the shift in body fat distribution to a more central location (5)(6)(7) and diminishes the loss of muscle strength (8)(9)(10)(11)(12)(13)(14)(15). Unfortunately, HRT use is accompanied by adverse side effects, such as an increased risk of breast cancer and cardiovascular disease (16), and for this reason its long-term use is not advocated.…”
Section: Introductionmentioning
confidence: 99%